THEORETICAL STUDY OF INTEGRATED CROWN ETHERS AND THEIR COMPLEXES WITH SOME TRANSITION AND LANTHANIDE IONS - Mahdi, Basim (Iraqi Journal of Science, 2024)
Geometrical parameters, ultraviolet and vibrational frequencies, relative stabilities, and heat of association of the six crown ethers (12O4, 12N4, 12S4, 12O2N2, 12O2S2, 12N2S2) were calculated by HF/STO-6G and HF/6-31G level of theory. The energies were calculated by single-point MP2 method using polarized 6-31G basis functions. The potential energy surface and HOMO-LUMO of these ligands indicate a remarkable change in electron density of 12O4 when nitrogen and sulfur atoms replaced the oxygen atoms which result in a major change in their ion selectivity toward transition (Co2+ , Ni2+ , Cu2+ , Rh2+ , and pd2+ ) and lanthanide (Nd2+ , Sm2+ , Eu2+ , Tm2+ , Yb2+ ) ions . The free ligands 12N4 and I2N2S2 were unstable in gas phase through geometry optimization but they are stable through complexation calculations. The heats of association with A-type and B-type ions were calculated by MMplus. In aqueous solution the 12N4 and 12S4 showed a high selectivity for Pd2+, Cu2+ions while the ligand 12O4 preferred to select Pd2+ and Rh2+ ions. The six ligands showed the same tendency for the lanthanide metal ions in the gas phase but they behave in a different manner in the aqueous phase. The theoretical IR vibrational spectra showed that Pd-N stretching, Pd-O stretching, and Pd-S stretching have a similar values within the range 603-616 cm-1.